E-Grocery Retailing Mobile Application: Discerning Determinants of Repatronage Intentions in an Emerging Economy. Issue 19 (26th November 2021) - Singh, Pratibha; Gupta, Manali; Kumar, Amresh; Sikdar, Pallab; Sinha, Neena
ABSTRACT: The study attempts to identify the influential antecedents of customer satisfaction and repatronage intentions in the context of e-grocery retailing through mobile applications. Literature survey based on qualitative thematic approach was adopted for the study. The reviewed articles were selected based on Critical Appraisal Skills Programme (CASP) framework. The model was subjected to reliability and validity determination through Confirmatory Factor Analysis (CFA). The hypotheses were tested through Structural Equation Modeling (SEM). SEM results revealed that out of the four proposed antecedents i.e. online tracking, design aesthetics, online rating & review, and perceived security risk, the initial three bear significant positive causal relationship with customer satisfaction. The existing study gives a perspective of e-grocery retailing based mobile applications in an emerging market, which is a departure from the past studies which are based on developed markets characterized by higher technology penetration and awareness amongst inhabiting populace.